ANALISIS KESTABILAN DAN KONTROL OPTIMAL MODEL LESLIE-GOWER FUNGSI RESPON HOLLING III DENGAN PEMANENAN PADA POPULASI PREDATOR DAN PREY - Himmatul Ulya Febriyanti; Syamsuddin Toaha; Kasbawati Kasbawati (Jurnal Matematika, Statistika dan Komputasi, 2019)
This article modified the leslie-gower model on harvesting with predator and prey population. This study aims at construct a modification of leslie-gower model with holing III response function. In addition, there is an effort harvesting in predator and prey population, analyzing an equilibrium point, finding bionomic equilibrium and the condition where the present value is maximum from net income by controlling harvesting in both populations. In the modified leslie-gower model there is an equilibrium point  which is asymptotically stable and when there have harvesting, the equilibrium point  is also asymptotically stable. Bionomic equilibrium from harvesting on the modified leslie-gower model is maximizing the profit function π of harvesting on a model with the maximum pontryagin principle resulting an optimal equilibrium) affected by instantaneous rate of discount δ.